Exploring potential impacts of hydraulic fracturing (fracking) on groundwater contamination in the Karoo: perspectives on institutional capabilities in water management in South Africa - Chisebe, Khumbelo Britney (My University, 2017)
Hydraulic fracturing in the Karoo is said to be a game changer of energy sector in South Africa, but it is said to pose potential groundwater contamination. Therefore the aim of the study was to investigate the extent to which current institutional set up in South Africa can deal and address potential environmental challenges that are associated to fracking. The study was particularly interested in investigating the institutional capabilities in the context of water management. The literature review of this study showed that water resource is a major environmental concern that revolves around hydraulic fracturing, including the water resources use and potential contamination. In addition, it should be considered that hydraulic fracturing is a new mining process in South Africa and Africa as a whole with controversial mining techniques and environmental impacts involved within this process. The review indicates that the biggest issue with proposed hydraulic fracking mining process in the Karoo is if the South African Government has taken into consideration the resources, infrastructures and skills to execute the process successfully. The literature asserts that even if proper enforcement of any regulations on this rapidly expanding industry will still be difficult as the regulation is insufficient due to certain explicit exemptions. In South Africa, the starting point for hydraulic fracturing and the associated regulations that governs fracking, is the recognition of an argument that South Africa does not possess any fracking specific laws, guidelines or even polices. Research participants were asked to give their views on the research topic by answering the semi structured interview questions. Data from the semi-structured interviews and literature review was analysed and discussed to address the research questions. The results of the investigation confirmed that there was no any legislation in place to govern this mining process in South Africa. Currently there are legislations which are under review and development to also address hydraulic fracking and the protection of water resources. The government should also involve other research institutes in the drafting and decision making of the legal institute governing hydraulic fracking to ensure that all gaps are identified before fracking can be permitted in the Karoo.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Environmental Science. with Witwatersrand University, Johannesburg, South Africa, (School of Geography, Archaeological and Environmental Science within the Faculty of Science) 2nd June 2017.
Keywords: Water--Pollution--South Africa; Water--Management; Hydraulic fracturing--Environmental aspects--South Africa--Karoo